Agent-based modelling of urban land-use development: modelling and simulating households and economic activities location choice. (24th April 2019) - Bouanan, Youssef; Zerguini, Seghir; Gaussier, Nathalie
This article aims to respond to growing concerns about sustainable urbanisation, which in recent years have generated a need for prospective assessment in the field of transport and land-use planning, by predicting future land-use development. We introduce a land use model (part LU of a land use transport interaction model) which aims to simulate households and economic activities location choice within an urban system. We use the agent-based approach to simulate location choices to account for land use changes and to estimate residential and economic activities location. This is a dynamic bottom-up approach with the households and the firms as their basic components. The MUST-B model considers the agents' location choices according to the utility theory and the equilibrium between real estate supply and demand. The model is used to simulate urban land-use development in the urban area of Bordeaux, France.